Keputusan investasi, intellectual capital, struktur modal, dan islamic social reporting terhadap nilai perusahaan: Peran good corporate governance sebagai moderasi - Rahayu, Dwi Putri; Saifudin (Journal of Accounting and Digital Finance, 2024)
This study aims to determine the effect of Investment Decisions, Intellectual Capital, Capital Structure and Islamic Social Reporting on Company Value with Good Corporate Governance as a moderating variable. The population in this study were companies listed on JII for the 2019-2022 period. The purposive sampling method was used in this study. From this method, 19 companies were obtained that met the criteria from a total of 19 companies during the four-year observation period. The total sample in the study was 76 companies. The data analysis method used panel data regression analysis. The results showed that Investment Decisions and Capital Structure had a negative effect on Company Value, Intellectual Capital and ISR had a positive effect on Company Value; GCG was unable to moderate the effect of Investment Decisions, Capital Structure, and ISR on Company Value, GCG was able to moderate the effect of Intellectual Capital on Company Value, and GCG hurt Company Value.